Composition of intestinal ciliate fauna of free-ranging African elephants in Tsavo West National Park, Kenya - Vincent Obanda; Isaac Lekolool; John Kariuki; Francis Gakuya (Pachyderm)
This study aimed at surveying intestinal protozoan ciliates of the African elephant (Loxodonta africana) in Tsavo West National Park, Kenya. Faecal samples of seven elephants chemically immobilized for translocation were collected opportunistically and flotation-sedimentation techniques used to assess the presence of ciliates. Identification of ciliates was based on morphological features such as shape, presence and morphology of external spines and lobes, micro- and macronuclei, and internal skeletal plates. Seven ciliate families and 27 genera were found in the faecal samples of the elephants. The families included Blepharocorythidae, Buetschliidae, Cycloposthiidae, Isotrichidae, Ophryoscoleciidae, Paraisotrichidae and Troglodytellidae. The dominant families were Buetschliidae with nine ciliate genera and Cycloposthiidae with eight. These ciliates in the caecum and colon of elephants are similar to those in the rumen and reticulum of ruminants. They digest plant fibres (principally cellulose and hemicellulose) that otherwise could not be used since elephants have no fibre-digesting enzymes of their own. This preliminary information will guide comparative studies on the rumen ciliate diversity and population of various hosts in different regions.